The Effectiveness of Different Decimals of Iranian Stock Market Returns from the Asymmetric Effects of Exchange Rate and Oil price Shocks in the Presence of Covid-19 - Masoumeh Shirinpour; Gholamali Haji; Ahmad Sarlak; Hamidreza Alipour (Environmental Energy and Economic Research)
The current research was conducted with the aim of investigating the effect of asymmetric shocks in the exchange rate and oil price on the performance of the Iranian stock market using monthly data from 2011 to 2021. the quantile regression model is examined in deciles ranging from 0.1 to 0.9. The results show that the quantile estimates were not symmetrical, but in other conditions such as recession, normal, boom and strong growth, oil shocks had a significant negative impact on stock market returns. The impact of exchange rate shocks on stock market returns was not significant in severe recession conditions. But in the conditions of recession, normal, boom and high boom, exchange rate shocks have a positive and significant effect on the performance of the Iranian stock market. In addition, in this research, the effect of exchange rate and oil shocks during the COVID-19 epidemic was analyzed, which had a significant effect on the effectiveness of oil shocks on stock returns. This asymmetric effect was observed in different negative and significant deciles. Therefore, it can be seen that fluctuations in the global oil price and exchange rate expose some of Iran's key indicators, including the capital market, to instability.